Improving Academic Achievement What School Counselors Can Do - Brown, Duane; ERIC Clearinghouse on Counseling and Student Services (Greensboro, NC : ERIC Clearinghouse on Counseling and Student Services, 1999)
The school reform movement has been a major societal and political agenda item for nearly two decades. As a result of the pressure stemming from the movement to make schools more effective, many changes have occurred. The most obvious of these changes is an increased emphasis on assessment. Furthermore, school counselors, like teachers and administrators, are now expected to play an important role in the school reform movement. This digest is designed to outline a number of strategies and techniques that school counselors can use to meet the challenge of improving student achievement. One strategy that is highlighted is that of improving school climate. School counselors can improve the climate of their schools by advocating for policies that promote rather than detract from the personal and educational development of students. Counselors are also encouraged to draw from a vast array of interventions that will help students increase their academic achievement. These interventions include behavioral contracts, study skills groups, time management training, classroom guidance units aimed at improving test taking skills, and achievement motivation groups. The final technique advocated is that of involving parents through parent consultation and parent education classes. (Contains five references.) (GCP)
Availability: ERIC Counseling and Student Services Clearinghouse, University of North Carolina at Greensboro, 201 Ferguson Building, P.O. Box 26171, Greensboro, NC 27402-6171. Tel: 336-334-4114; Tel: 800-414-9769 (Toll Free); Fax: 336-334-4116; e-mail: ericcass@uncg.edu; Web site: <http://ericcass.uncg.edu>.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: ED-99-CO-0014.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Behavioral Objectives; Counseling Techniques; Counselor Role; Dropouts; Educational Assessment; Educational Change; Educational Environment; Elementary Secondary Education; High Risk Students; Intervention; Merit Pay; Parent Participation; School Counselors; Student Evaluation; ERIC Digests; ERIC Publications; ERIC Digests in Full Text